KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN RUMAH SAKIT SELASIH KABUPATEN PELALAWAN - Mey Sarah Azhari; Lilik Istikhairyah (LPPM Universitas Awal Bros, 2020)
Health services are an integral part of hospitals, which have a very strategic position in an effort to improve the quality of service for consumers who come to the hospital. The purpose of this systematic review was to describe the relationship between caring and therapeutic communication with service quality in hospitals. The method used by searching the article database consists of quantitative studies collected from the 2015-2020 scholar base database. The results show that caring is good so that patients feel satisfied and good therapeutic communication so that patients feel satisfied with the quality provided in health services. The conclusion that the quality of health services has an influence on the frequency of patient satisfaction levels, the better the quality of health services, the better the frequency of patient satisfaction levels. So, there is a significant relationship between caring and therapeutic communication with the quality of nursing services.